INVENTARISASI JAMUR PADA BUAH TOMAT (Lycopersicum esculentum Mill) DIBEBERAPA PASAR DI KOTA PADANG Oleh Yuniar1 - Yuniar, Yuniar; Periadnadi, Periadnadi; Megahati, RRP. (STKIP PGRI Sumbar, 2014)
Abstract Tomato (Lycopersicum esculentum Mill) is one of the horticultural plants was found around Peru, Ecuador, Bolivia and quickly spread in to all of world. Tomatoes consist of several nutrients such as vitamins A and C. Tomatoes havealso high content of water and soft texture, therefore tomatoes can not be saved for a long time, they are easy to be damage after harvesting caused by handling and transporting. They are also easy to be contaminated by microorganism such as fungus and bacteria. It will make the tomato decomposed and decayed. The purpose of this research is to inventarisation of fungus found on tomatoes were sold in some markets in Padang. This research has done in laboratory of Microbiology of the Department o f Biology, faculty of Mathematics and Natural Sciences Faculty, Andalas University since February until March 2014. The research used descriptive survey method, and the samples were collected by purposive sampling. The fungi isolated in medium PDA and characterised macros- and microscopicaly for the identification. The result found three species of fungus, they are Aspergillus niger, Aspergillus parasiticus, Penicillium italicum and Mucor sp